KEBIJAKAN TINDAK PIDANA TERHADAP PELAKU PENGGELAPAN MOBIL SEWA DI CV ALIF TRANS - Moch Miftakhul Mustofa; Ifahda Pratama Hapsari (Program Magister Ilmu Hukum Universitas Ekasakti, 2023)
The development of information technology has now changed people's lifestyles, including in transportation. Various transportation developments both online and in person. Many people live a luxurious lifestyle to show that they have a different class but not everyone can meet these needs because of expensive prices and car maintenance. So many rental car rentals, but it is very unfortunate that in practice rental services are targets or targets of crime by people. irresponsible. This is marked by the frequent occurrence and criminal acts of car fraud or embezzlement committed by users of car rental services. Embezzlement is someone who abuses rights or abuses trust where the trust is obtained without any elements against the law. Car embezzlement is one of them. an unlawful act that may be subject to a criminal offense. The case occurred in the Cerme sub-district, Gresik district, in the ALIF TRANS car rental, in the agreement the tenant rented for 1 month but after one month the car was not returned, it turned out that the car was pawned on the other side. This is a violation of criminal law. This crime is an unlawful act committed by tricking or hiding a rented car from the owner. In this article, we will explain the articles in the Criminal Code that can be applied in cases of embezzlement of rental cars, such as Articles 372, 1548, and CHAPTER XXVI. The method used in this study uses a type of normative juridical research, namely research according to the book of laws Criminal Code. There is a need for a policy approach that must be taken, namely a combination of efforts to deal with crime with a penalty (after it has occurred) and (before it has occurred). Penal efforts or criminal policies are divided into penal efforts and non-penal efforts, penal efforts are efforts that are repressive after a crime has occurred, while non-penal efforts are crime prevention efforts that focus more on preventive efforts.